Assessment of different crosslinked mechanisms on PVA-based membranes to achieve water resistant properties with iron imprinting sites - Ihsan Alfikro; Jorena Jorena; Octavianus Cakra Satya; Erry Koriyanti; Fiber Monado; Idha Royani (Chimica Techno Acta)
Water-resistant PVA (polyvinyl alcohol) electrospun membranes with different crosslinking mechanisms were synthesized using the facile electrospinning technique. The crosslinking mechanisms were differentiated by introducing 2 different functional groups of different crosslinker agents into the molecular structure of the membrane. The evaluation of water resistance was conducted by both micro- and macro-structural analyses, such as Fourier Transform Infrared spectroscopy (FTIR), Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), water contact angle (WCA), and immersion test. Infrared spectra confirmed the formation of new bands at around 1700 cm-1, which are acetal or ester groups, indicating the successful crosslinked process. Additionally, the lowered intensity of hydroxyl groups also signifies that the membrane is water-resistant. The XRD patterns showed the signature peak of PVA at the angle of 20°. Furthermore, the reduction in iron content, as shown by EDS spectra, was attributed to the surface imprinting process. SEM images displayed the formation of nanofibers, with mean diameters of 103 nm and interconnecting nanobead structures. The results showed that WCA was significantly enhanced, up to 91°, with minor loss in structure during water immersion test for 24 h. These findings confirm the hydrophobic characteristics of the membranes and their potential application in water-related fields.